Preparation and application of donut-structured hydrogel

Through the preparation method of donut structure hydrogel, the problem of insufficient recyclability of existing seawater desalination materials is solved, and efficient and recyclable seawater desalination effect is achieved, which is suitable for seawater treatment of different temperatures and components.

CN119639030BActive Publication Date: 2025-04-25CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510169377.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-25
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

The existing hydrogel-based desalination materials have insufficient recyclability and are difficult to maintain durability and efficiency in use environments.

Method used

Using the preparation method of donut structure hydrogel, the donut structure hydrogel is formed by mixing ZrOCl2·8H2O and fumaric acid, and ultrasonic dispersing with multi-wall carbon nanotubes and then hydrothermal treatment is carried out, followed by modification with acrylic chloride and thermally crosslinking treatment with polyvinyl alcohol, tapioca starch and crosslinking agent to form a donut structure hydrogel with temperature responsiveness and high evaporation efficiency.

Benefits of technology

The hydrogel exhibits high evaporation efficiency, temperature responsiveness and good recyclability in the field of seawater desalination, and can efficiently desalinate seawater of different temperatures and components, and maintain efficient operation under long and high load conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639030B_ABST
    Figure CN119639030B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of hydrogels, and mainly relates to the preparation and application of a donut-structured hydrogel. The present invention aims to solve the problem of insufficient recyclability of existing hydrogel-based seawater desalination materials. The present invention obtains a pretreated precursor by mixing ZrOCl2·8H2O and fumaric acid, and then ultrasonically dispersing the mixture with multi-walled carbon nanotubes; the pretreated precursor is subjected to hydrothermal treatment, and modified with acryloyl chloride to obtain a modified MOF801@CNT; the modified MOF801@CNT is subjected to thermosensitive cross-linking treatment with polyvinyl alcohol, cassava starch and a cross-linking agent to obtain a donut-structured hydrogel. The hydrogel has high application value in the field of seawater desalination, has self-regulation of temperature response, high evaporation efficiency and can be recycled, and can efficiently desalinate seawater of different temperatures and compositions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogels, and mainly relates to the preparation and application of a donut-structured hydrogel. Background Art

[0002] Hydrogel is a new type of material that has attracted much attention and has been used in various fields. Hydrogel has a unique spatial hydrophilic network structure. While being highly hydrophilic, its functional properties can be deeply customized by introducing functional groups and changing the degree of cross-linking, which expands the scope of application of hydrogel. These characteristics of hydrogel give it considerable application prospects in the field of seawater desalination.

[0003] Metal organic framework (MOF, the same below) material is also a new type of material with rich functionality. It has an ultra-high specific surface area and a large number of microscopic and mesoscopic pores. It can also achieve a variety of functions by introducing different skeleton metal ions and organic groups. In recent years, various studies on the composite of hydrogel and MOF materials have received increasing attention in the academic circle. The combination of the two materials can regulate its functionality through more abundant means and achieve more dimensional functional deep customization. Similarly, these characteristics of MOF materials make it also have extremely high application value in the field of seawater desalination technology.

[0004] At present, the academic circle and the industrial community have also conducted a lot of research in this direction and made some progress. For example, Chinese patent CN115748257B proposes a method for rapid preparation of porous composite hydrogels and their application in photothermal desalination. A porous composite hydrogel treated with radiation cross-linking is designed, and its pore structure is highly connected, open and adjustable, which can ensure the continuous evaporation process of seawater. The problem with this invention is that it cannot guarantee the recyclability and durability in the use environment. Chinese patent CN115433377B provides a solar desalination hydrogel and a preparation method thereof, which uses a plasma method to efficiently prepare hydrogels, and has a high photothermal conversion efficiency, low cost and environmental pollution. This invention overcomes the problem of low efficiency in preparing hydrogels by chemical methods, but there is still a problem of insufficient recyclability. Chinese patent CN109647231B proposes a graphene oxide / MOF composite membrane and its preparation method and application, introduces polyvinyl alcohol between graphene oxide layers, and pre-crosslinks metal ions with the membrane structure in advance, thereby increasing the water flux of the membrane and further improving the separation performance and stability of the membrane. The problem with this invention is that the water flux of the simple MOF membrane structure is not enough to meet the requirements of the seawater desalination process, and the durability and recyclability cannot be guaranteed.

[0005] In particular, in the field of seawater desalination, the composite MOF hydrogel material has high water absorption, high stability and excellent desalination efficiency. It can not only rely on the rapid water absorption characteristics of the hydrogel to increase water flux, but also rely on MOF to effectively intercept inorganic salt ions and other impurities. At the same time, by regulating the performance of different units of the material, it can solve different technical problems in the process in a targeted manner, providing a potential solution for alleviating the freshwater crisis and achieving sustainable development of water resources.

[0006] Currently, the insufficient recyclability of hydrogel-based desalination materials remains a major challenge faced by relevant researchers.

[0007] Therefore, the preparation and application of donut-structured hydrogel are proposed. Summary of the invention

[0008] The purpose of the present invention is to provide a preparation and application of a donut-structured hydrogel. The present invention obtains a pre-treated precursor by mixing ZrOCl2·8H2O and fumaric acid, and then ultrasonically dispersing the mixture with multi-walled carbon nanotubes; the pre-treated precursor is subjected to hydrothermal treatment, and modified with acryloyl chloride to obtain a modified MOF801@CNT; the modified MOF801@CNT is subjected to a thermosensitive cross-linking treatment with polyvinyl alcohol, cassava starch and a cross-linking agent to obtain a donut-structured hydrogel. The hydrogel has high application value in the field of seawater desalination, has temperature-responsive self-regulation, high evaporation efficiency and can be recycled, and can efficiently desalinate seawater of different temperatures and compositions.

[0009] To achieve the above object, the present invention provides the following technical solutions:

[0010] refer to Figure 1 The preparation flow chart shown in the figure shows a method for preparing a donut structure hydrogel, comprising the following steps:

[0011] Unless otherwise specified, the parts used in the present invention are parts by mass.

[0012] ZrOCl2·8H2O and fumaric acid were ultrasonically dissolved in solvent A, multi-walled carbon nanotubes (MWCNTs, the same below) were added, and a pre-treated precursor was obtained after ultrasonic dispersion;

[0013] The pretreated precursor is subjected to hydrothermal treatment, washed and dried to obtain a MOF precursor;

[0014] The MOF precursor is modified with acryloyl chloride to obtain a modified MOF;

[0015] The modified MOF was grafted to obtain MOF801@CNT;

[0016] MOF801@CNT was subjected to thermosensitive cross-linking treatment with polyvinyl alcohol (PVA, the same below), cassava starch and a cross-linking agent to obtain a donut-structured hydrogel (PTMC, the same below).

[0017] Preferably, the ultrasonic dissolution process is: add 20-30 parts of ZrOCl2·8H2O and 10 parts of fumaric acid to 300 parts of solvent A, and treat at an ultrasonic power of 200 W and a frequency of 50 kHz for 5 minutes to obtain a mixed solution A.

[0018] Preferably, the ultrasonic dispersion process is: 8 parts of MWCNTs are added to the mixed solution A, and treated at 40° C. with an ultrasonic power of 300-500 W and a frequency of 60 kHz for 30 minutes to obtain a pretreated precursor.

[0019] Preferably, solvent A comprises: N,N-dimethylformamide and formic acid, wherein the volume ratio of N,N-dimethylformamide to formic acid is 19:8.

[0020] Preferably, the hydrothermal treatment process is as follows: 350 parts of the pretreated precursor are added to a hydrothermal kettle, the temperature is increased to 130°C at a rate of 10°C / min, and the temperature is kept at autogenous pressure for 7 hours to obtain a hydrothermal precursor; the hydrothermal precursor is cooled to 25°C and centrifuged at 6000rpm for 5 minutes, the supernatant is removed and the solid product is retained, and after alternately washing with methanol and N,N-dimethylformamide, it is placed at 60°C and vacuum dried at a vacuum degree of 95kPa for 12 hours to obtain a MOF precursor.

[0021] Preferably, the modification process is as follows: 20 parts of MOF precursor are dispersed in 100 parts of dichloromethane, and stirred at a speed of 500 rpm in an ice water bath to obtain a reaction solution A; 30 parts of acryloyl chloride solution are slowly added dropwise to the reaction solution A, and a reaction solution B is obtained after the addition is completed, wherein the dropping rate of the acryloyl chloride solution is 3-5 mL / min; the reaction solution B is heated to 25°C, stirred at a speed of 200 rpm for 16-18 hours, and after removing the solvent, the modified MOF is obtained by washing and drying.

[0022] Preferably, the acryloyl chloride solution comprises: acryloyl chloride, dichloromethane, acetonitrile and a capture agent; the capture agent comprises: triethylamine and pyridine, wherein the volume ratio of triethylamine to pyridine is 3:1; the preparation method of the acryloyl chloride solution is: dissolving 2-3 parts of acryloyl chloride in 50 parts of dichloromethane in an ice water bath, stirring at a speed of 350 rpm, then adding 1 part of the capture agent, and then adding 75 parts of acetonitrile, and mixing evenly to obtain the acryloyl chloride solution.

[0023] Preferably, the grafting process is as follows: 20 parts of modified MOF are dispersed in 100 parts of initiator solution, stirred at 200 rpm for 20 minutes at 25°C, 5 parts of N-isopropylacrylamide are slowly added, the mixture is heated to 75°C after being evenly mixed, and the reaction is stirred at 200 rpm for 20 hours, and the solvent is removed and then washed and dried to obtain MOF801@CNT; the initiator solution comprises: azobisisobutyronitrile, potassium persulfate, tetrahydrofuran and N,N-dimethylformamide, wherein the amount of azobisisobutyronitrile added is 3 parts, the amount of potassium persulfate added is 2 parts, the amount of tetrahydrofuran added is 45 parts, and the amount of N,N-dimethylformamide added is 50 parts.

[0024] Preferably, the process of thermosensitive crosslinking treatment is: 2.5 parts of MOF801@CNT are dispersed in 100 parts of deionized water, treated at 25°C with an ultrasonic power of 300 W and a frequency of 50 kHz for 30 minutes, and then 25 parts of PVA and 25 parts of cassava starch are added, stirred at 70°C at a speed of 400 rpm for 2 hours, and then 20 parts of a crosslinking agent are added. After mixing evenly, the mixture is allowed to stand at 40°C for 2 hours to obtain PTMC; the crosslinking agent includes: 10 parts of hydrochloric acid and 10 parts of glutaraldehyde solution, wherein the mass concentration of hydrochloric acid is 5%, and the mass concentration of glutaraldehyde is 5%.

[0025] Preferably, the molecular weight of PVA is 80,000-100,000, and the molecular weight of cassava starch is 600,000-700,000.

[0026] An application of a donut-structured hydrogel comprises the application of the PTMC prepared by the invention in a seawater desalination process; the PTMC is placed on the seawater surface, the bottom of the PTMC is in contact with the seawater, and interface photoevaporation is performed under the drive of solar energy.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The introduction of metal organic framework (MOF, the same below) structure into the hydrogel matrix combines the hydrophilicity of the hydrogel with the porous structure of the MOF material and the excellent photothermal conversion performance, significantly improving the water enrichment capacity and evaporation efficiency. The three-dimensional hydrophilic network of the hydrogel can promote the replenishment of water molecules and accelerate the generation of water vapor, and the loaded MOF material can effectively select ions and has excellent light absorption capacity. The synergistic effect of the two greatly improves the evaporation efficiency of seawater desalination and the water quality of the resulting desalinated water.

[0029] 2. By introducing MWCNTs into MOF materials, and using ultrasonic dispersion and common hydrothermal treatment to fully load MOF materials, MWCNTs are made to fully load MOF materials. The unique structure of MWCNTs facilitates the rapid transmission of water molecules, and has good chemical stability, and can maintain stable performance under harsh conditions such as high temperature, acid and alkali. MOF has an ultra-high specific surface area and porous structure, which helps to efficiently capture and filter ions and impurities in seawater, providing good separation performance. The effective combination of the two makes PTMC show higher ion selectivity and water flux in seawater desalination, and the chemical stability is greatly improved, and it can maintain efficient operation under long-term and high-load conditions.

[0030] 3. The use of acryloyl chloride to modify the MOF precursor not only improves the ion selectivity of the MOF material, but also significantly enhances the chemical stability and adsorption performance of the MOF material, and improves the pore structure of the MOF material. Furthermore, the modified MOF material modified with acryloyl chloride can be efficiently connected with the hydrogel through the polyacrylamide (PNIPAm, the same below) structure during the subsequent processing process, which helps to form a composite structure with multiple functions.

[0031] 4. The modified MOF was grafted and a PNIPAm structure with temperature responsiveness was introduced. The hydrogel structure containing PNIPAm has good hydrophilicity at lower temperatures, and its hydrophilicity is significantly reduced above its lower critical solution temperature (LCST, about 32°C). This property enables it to effectively regulate the passage of water molecules during the desalination process, thereby achieving efficient water separation. Grafting N-isopropylacrylamide on MOF allows the PNIPAm structure to simultaneously regulate the functions of the hydrogel unit and the MOF unit, achieving temperature responsiveness of the desalination function and effectively extending the service life of the composite hydrogel.

[0032] 5. Thermosensitive cross-linking treatment was performed on MOF801@CNT, PVA, cassava starch and cross-linking agent to prepare in situ composite hydrogels with good light absorption performance and temperature response characteristics. Thermosensitive cross-linking treatment effectively combined the polymerization process of PNIPAm and the gelation process of PVA-cassava starch hydrogel, so that the polymerization process and gelation process of N-isopropylacrylamide influenced each other, thereby preparing a hydrogel structure with self-healing properties, which can maintain excellent recyclability in the case of complex seawater desalination processes with different temperatures and components. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a process flow chart of the preparation method of PTMC in the present invention.

[0034] Figure 2This is a transmission electron microscope (TEM, the same below) image of MOF801@CNT in the present invention.

[0035] Figure 3 This is a scanning electron microscope (SEM, the same below) image of MOF801@CNT in the present invention.

[0036] Figure 4 It is the SEM image of PTMC in the present invention.

[0037] Figure 5 It is the ultraviolet-visible (UV-Vis, the same below) absorption spectrum image of PTMC and polyvinyl alcohol-cassava starch hydrogel (PT, the same below) in the present invention and the near infrared (NIR, the same below) spectrum image of PTMC. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be clearly and completely described below through some embodiments and experimental examples. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Reference Figure 1 The preparation flow chart shown in the figure, the present invention provides a highly environmentally friendly heat shrinkage resistant asphalt waterproof coating and a preparation method thereof, and the technical scheme is as follows:

[0040] The substance information involved in the present invention is as follows:

[0041] ZrOCl2·8H2O: CAS: 13520-92-8; Fumaric acid: CAS: 110-17-8; Multi-walled carbon nanotubes: CAS: 308068-56-6; Acryloyl chloride: CAS: 814-68-6; Polyvinyl alcohol: CAS: 9002-89-5; Cassava starch: CAS: 9005-25-8; Formic acid: CAS: 64-18-6; Methanol: CAS: 67-56-1; Acetonitrile: CAS: 75-05-8; Triethylamine: CAS: 121-44-8; Azobis(III) Isobutyronitrile: CAS: 78-67-1; Pyridine: CAS: 110-86-1; Dichloromethane: CAS: 75-09-2; N,N-dimethylacetamide: CAS: 127-19-5; Tetrahydrofuran: CAS: 109-99-9; N-isopropylacrylamide: CAS: 2210-25-5; Potassium persulfate: CAS: 7727-21-1; Dibutyl phthalate: CAS: 84-74-2; Hydrochloric acid: CAS: 7647-01-0; Glutaraldehyde: CAS: 111-30-8.

[0042] Example 1

[0043] 20 parts of ZrOCl2·8H2O and 10 parts of fumaric acid were added to 300 parts of solvent A, and treated at an ultrasonic power of 200 W and a frequency of 50 kHz for 5 minutes to obtain a mixed solution A; 8 parts of MWCNTs were added to the mixed solution A, and treated at an ultrasonic power of 300 W and a frequency of 60 kHz at 40°C for 30 minutes to obtain a pretreated precursor.

[0044] Wherein, solvent A is a mixed solvent of N,N-dimethylformamide and formic acid, and the volume ratio of N,N-dimethylformamide to formic acid is 19:8.

[0045] 350 parts of the pretreated precursor were added to a hydrothermal autoclave, heated to 130°C at a rate of 10°C / min, and kept warm for 7 hours under autogenous pressure to obtain a hydrothermal precursor; the hydrothermal precursor was cooled to 25°C and centrifuged at 6000 rpm for 5 minutes, the supernatant was removed and the solid product was retained. After alternately washing with methanol and N,N-dimethylformamide, it was placed at 60°C and vacuum dried at a vacuum degree of 95 kPa for 12 hours to obtain a MOF precursor.

[0046] 20 parts of MOF precursor were dispersed in 100 parts of dichloromethane, and stirred at 500 rpm in an ice-water bath to obtain reaction solution A; 30 parts of acryloyl chloride solution were slowly added dropwise to reaction solution A to obtain reaction solution B, wherein the dropping rate of acryloyl chloride solution was 3 mL / min; reaction solution B was heated to 25°C, stirred at 200 rpm for 16 hours, and after removing the solvent, the modified MOF was obtained by washing and drying.

[0047] The acryloyl chloride solution comprises acryloyl chloride, dichloromethane, acetonitrile and a capture agent; the capture agent comprises triethylamine and pyridine, wherein the volume ratio of triethylamine to pyridine is 3:1.

[0048] The preparation method of the acryloyl chloride solution is as follows: dissolving 2 parts of acryloyl chloride in 50 parts of dichloromethane in an ice water bath, stirring at a speed of 350 rpm, and then adding 1 part of a capture agent, mixing evenly, and then adding 75 parts of acetonitrile, mixing evenly to obtain an acryloyl chloride solution.

[0049] 20 parts of modified MOF were dispersed in 100 parts of initiator solution. After stirring at 200 rpm for 20 minutes at 25°C, 5 parts of N-isopropylacrylamide were slowly added. After mixing evenly, the temperature was raised to 75°C and stirred at 200 rpm for 20 hours. After removing the solvent, the mixture was washed and dried to obtain MOF801@CNT. The initiator solution included: azobisisobutyronitrile, potassium persulfate, tetrahydrofuran and N,N-dimethylformamide, wherein the amount of azobisisobutyronitrile added was 3 parts, the amount of potassium persulfate added was 2 parts, the amount of tetrahydrofuran added was 45 parts, and the amount of N,N-dimethylformamide added was 50 parts.

[0050] 2.5 parts of MOF801@CNT were dispersed in 100 parts of deionized water, treated at 25°C with an ultrasonic power of 300 W and a frequency of 50 kHz for 30 minutes, and then 25 parts of PVA and 25 parts of cassava starch were added, stirred at 70°C at a speed of 400 rpm for 2 hours, and then 20 parts of a cross-linking agent were added. After mixing evenly, the mixture was allowed to stand at 40°C for 2 hours to obtain PTMC; the cross-linking agent included: 10 parts of hydrochloric acid and 10 parts of glutaraldehyde solution, wherein the mass concentration of hydrochloric acid was 5%, and the mass concentration of glutaraldehyde was 5%.

[0051] Among them, the molecular weight of PVA used is 80,000, and the molecular weight of cassava starch is 700,000.

[0052] Examples 2-18 refer to the process flow and experimental methods of Example 1, but some parameters are changed, which are specifically summarized in Table 1.

[0053] Table 1 Process parameters adjusted in Examples 1-18

[0054]

[0055] As shown in the experimental parameters of Table 1, Examples 1-18 show the general preparation process and experimental conditions of PTMC.

[0056] In order to verify the necessity of some technical solutions in the present invention for achieving the technical effects of the present invention, some comparative examples of the present invention will be shown and described below.

[0057] Comparative Example 1

[0058] Different from Example 1, MOF801@CNT was not prepared, and PVA-cassava starch hydrogel was directly prepared and subjected to thermosensitive cross-linking treatment. The prepared hydrogel was called PT.

[0059] Comparative Example 2

[0060] Different from Example 1, the ultrasonic dispersion process is not performed, and the ZrOCl2·8H2O, fumaric acid and MWCNTs are directly dissolved and then hydrothermally treated.

[0061] Comparative Example 3

[0062] Different from Example 1, no co-hydrothermal treatment process is performed, and the solid prepared by co-hydrothermal treatment of ZrOCl2·8H2O and fumaric acid is simply blended with MWCNTs to replace the MOF precursor in the subsequent process.

[0063] Comparative Example 4

[0064] Different from Example 5, no modification treatment is performed, and only acryloyl chloride and MOF precursor are blended and then the subsequent process is carried out.

[0065] Comparative Example 5

[0066] Different from Example 5, no modification treatment was performed, no acryloyl chloride was added, and an equal amount of MOF precursor was used instead of the modified MOF for the subsequent process.

[0067] Comparative Example 6

[0068] Different from Example 11, no grafting treatment is performed, and only N-isopropylacrylamide is blended with the modified MOF and then the subsequent process is performed.

[0069] Comparative Example 7

[0070] Different from Example 11, no grafting treatment was performed, and no N-isopropylacrylamide was added, and an equal amount of modified MOF was used to replace MOF801@CNT for subsequent processes.

[0071] Comparative Example 8

[0072] Different from Example 15, no heat-sensitive cross-linking treatment is performed, and polymerization reaction is performed first, and then gelation reaction is performed. The specific operation steps are as follows:

[0073] 2.5 parts of the MOF801@CNT were dispersed in 100 parts of deionized water, treated at 25°C with an ultrasonic power of 300 W and a frequency of 50 kHz for 30 minutes, and then 10 parts of a cross-linking agent were added, and stirred at 70°C at a speed of 400 rpm for 2 hours; then 25 parts of PVA and 25 parts of cassava starch were added, and stirred at 70°C at a speed of 400 rpm for 2 hours, and finally 10 parts of a cross-linking agent were added, mixed evenly, and allowed to stand at 40°C for 2 hours to obtain the final product.

[0074] Comparative Example 9

[0075] Different from Example 15, no thermosensitive cross-linking treatment was performed, and the MOF801@CNT after the polymerization reaction was simply mixed with the PVA-cassava starch gel. The specific operation steps are as follows:

[0076] 25 parts of PVA and 25 parts of cassava starch were dispersed in 50 parts of deionized water, stirred at 400 rpm at 70° C. for 2 hours, 10 parts of a cross-linking agent were added, and the mixture was allowed to stand at 40° C. for 2 hours to obtain a PVA-cassava starch gel.

[0077] 2.5 parts of the MOF801@CNT were dispersed in 50 parts of deionized water, treated at 25°C with an ultrasonic power of 300 W and a frequency of 50 kHz for 30 minutes, and then 10 parts of a cross-linking agent were added, stirred at 70°C at a speed of 400 rpm for 2 hours, and PVA-cassava starch gel was added and mixed evenly to obtain the final product.

[0078] Experimental Example 1

[0079] The MOF801@CNT prepared in Example 1 was subjected to TEM and SEM tests, and the results are as follows: Figure 2 and Figure 3 shown.

[0080] The PTMC prepared in Example 1 was subjected to SEM testing, and the results were as follows: Figure 4 shown.

[0081] The PTMC prepared in Example 1 and the PT prepared in Comparative Example 1 were tested by UV-Vis spectrum and NIR spectrum. The results are as follows: Figure 5 shown.

[0082] The PTMC prepared in Example 1 and the PT prepared in Comparative Example 1 were subjected to a seawater desalination experiment to detect their evaporation rates and the quality of evaporated water.

[0083] The specific steps of the seawater desalination experiment are as follows:

[0084] The hydrogel was prepared into a circular film with a thickness of 2.5 mm and a diameter of 15 cm. Seawater was injected into a cylindrical container with an inner diameter of 15 cm, and the hydrogel was spread on the upper surface of the seawater. The average sunlight intensity was 1 sun for 4 hours, and the condensed water was collected, the water evaporation rate was calculated, and the inorganic salt content in the condensed water was detected. The ambient temperature was 25±1℃ and the humidity was 65±5%.

[0085] The water evaporation rate is calculated as:

[0086] Water evaporation rate [kg / (m 2 h)] = condensed water volume (kg) / [(evaporation surface area (m 2 )·Time (h)]

[0087] Among them, the salinity of seawater used is 34.87‰.

[0088] according to Figure 2 , Figure 3 and Figure 4 From the microscopic morphologies of MOF801@CNT and PTMC shown, it can be seen that MOF801@CNT has a composite structure of nanoparticles and nanowires, the structures of MOF and carbon nanotubes are deeply integrated, and the surface of MOF is uniformly modified by polyacrylamide. The composite hydrogel presents an obvious donut structure, indicating that it has a three-dimensional hydrophilic structure and forms a composite material with MOF with a uniform structure.

[0089] according to Figure 5 From the UV-Vis spectrum and NIR spectrum test results shown, it can be seen that PTMC has a significant full-spectrum light absorption capacity compared to PT, and has extremely high absorption efficiency in the ultraviolet, visible and near-infrared wavelength ranges. Therefore, PTMC has a stronger photothermal conversion potential.

[0090] The results of the seawater desalination experiment are:

[0091] PTMC: water evaporation rate is 1.37kg / (m 2 ·h); the inorganic salt content is 3.7ppm.

[0092] PT: Water evaporation rate is 0.29kg / (m 2 ·h); the inorganic salt content is 68.2ppm.

[0093] In summary, the addition of MOF801@CNT makes the composite hydrogel have significant light absorption properties, thus showing a water evaporation rate much higher than that of pure hydrogel. And because MOF materials have excellent capture effects on inorganic salt ions, while accelerating the evaporation of seawater, it also ensures that the salinity of the evaporated water is extremely low.

[0094] Experimental Example 2

[0095] Referring to the specific steps of the hydrogel desalination experiment in Experimental Example 1, the hydrogels prepared in Examples 2-4 and Comparative Examples 2-3 were respectively subjected to seawater desalination experiments, and their water evaporation rates were calculated, and the inorganic salt content of the condensed water was detected and recorded in Table 2. At the same time, a blank control group experiment was conducted in which seawater was directly evaporated without using any film, and the results were recorded in Table 2.

[0096] At the same time, the photothermal conversion efficiency of different experimental groups was calculated and recorded in Table 2. The calculation method of photothermal conversion efficiency η is: η=mL / PSt, where m is the mass of condensed water; L is the heat of vaporization of water, at 25℃ and 1atm, L=2.26×10 6 J / kg; P is the incident light power density, which is equal to the average sunlight intensity in this experiment; S is the effective illumination area of ​​the hydrogel; and t is the effective illumination time.

[0097] The pH of the experimental seawater was adjusted to 3.5 with hydrochloric acid to simulate the harsh conditions of high acidity. The same test was performed on the hydrogels prepared in Examples 2-4 and Comparative Examples 2-3. The water evaporation rate, photothermal conversion efficiency and condensed water salt content were recorded. The results are summarized in Table 2.

[0098] Table 2 Desalination performance of hydrogels prepared in Examples 2-7 and Comparative Examples 2-3

[0099]

[0100] As shown in the desalination performance of the hydrogels prepared by different embodiments and comparative examples in Table 2, Examples 2-4 all have good photothermal conversion efficiency and desalination effect, and have excellent water evaporation rate and photothermal conversion efficiency in normal and high acid environments, and the salinity of condensed water is low. Due to the lack of ultrasonic dispersion in Comparative Example 2, MOF and MWCNTs failed to form a regular composite structure, the photothermal conversion efficiency was significantly reduced, and the salt content of condensed water was significantly increased. Due to the lack of common hydrothermal treatment in Comparative Example 3, the MOF structure and the carbon nanotube structure could not play a synergistic role, the photothermal conversion efficiency was lost to a certain extent, and a significant performance decline occurred in a high acid environment, which was attributed to the lack of MOF and carbon nanotube composite structures, which reduced the ion selectivity and water flux of the composite material to seawater, and the chemical stability was greatly reduced. Therefore, the composite structure formed by the effective combination of MOF and MWCNTs by ultrasonic dispersion and hydrothermal treatment can greatly improve the ion selectivity and water flux of the composite hydrogel, and make the hydrogel still highly stable in harsh chemical environments, and the desalination function is almost unaffected.

[0101] Experimental Example 3

[0102] Referring to the experimental steps and parameters of Experimental Example 2, a seawater desalination experiment was carried out on the composite hydrogels prepared in Examples 5-10 and Comparative Examples 4-5, and a comparative seawater desalination experiment with high-acid seawater was carried out. The water evaporation rate, photothermal conversion efficiency and condensed water salinity were recorded. The results are summarized in Table 3.

[0103] Table 3 Desalination performance of hydrogels prepared in Examples 5-10 and Comparative Examples 4-5

[0104]

[0105] As shown in the desalination performance data of the hydrogels prepared by Examples 5-10 and Comparative Examples 4-5 in Table 2, Examples 5-10 have excellent water evaporation rates and photothermal conversion efficiencies in both normal and high acid environments, and the salinity of the condensed water is low. Due to the lack of modification treatment in Comparative Example 4, the simple blending of acryloyl chloride and MOF cannot improve the surface structure of MOF, and is even equivalent to introducing small molecule impurities into the hydrogel structure, causing the photothermal conversion efficiency of the resulting composite hydrogel to decrease significantly, and the chemical stability and adsorption capacity to decrease significantly. However, in Comparative Example 5, there is no addition of acryloyl chloride at all. When the surface structure of MOF remains unchanged, the small molecules of acryloyl chloride will not become impurities, so the performance of the resulting hydrogel is slightly better than that of Comparative Example 5. Therefore, the surface modification treatment of MOF by acryloyl chloride has an important positive significance for the performance of the composite hydrogel. By improving the surface structure and pore structure of MOF, the chemical stability of the composite hydrogel and the adsorption performance of inorganic salt ions are enhanced, and active sites are provided for subsequent processes.

[0106] Experimental Example 4

[0107] Referring to the experimental steps of Experimental Example 2, a seawater desalination experiment was conducted on the composite hydrogels prepared in Examples 11-14 and Comparative Examples 6-7. The photothermal conversion efficiency and the salt content of the condensed water were recorded, and the results are summarized in Table 4.

[0108] In order to simulate the desalination effect under lower seawater temperature, the ambient temperature was changed to 0°C and a desalination experiment was carried out. The photothermal conversion efficiency and the salt content of the condensed water were recorded, and the results are summarized in Table 4.

[0109] In order to simulate the desalination effect under higher seawater temperature, the ambient temperature was changed to 35°C and a desalination experiment was carried out. The photothermal conversion efficiency and the salt content of the condensed water were recorded, and the results are summarized in Table 4.

[0110] Table 4 Desalination effect of composite hydrogel at different temperatures

[0111]

[0112] As shown in the data of the composite hydrogel desalination effect at different temperatures in Table 4, seawater at different temperatures has different performance requirements for the desalination process. When the seawater temperature is low, part of the energy of solar radiation will be lost in heating seawater. In this case, the hydrogel should have a higher water flux and light absorption rate to improve the photothermal conversion efficiency and use as much solar energy as possible to evaporate seawater; when the seawater temperature is high, the internal thermal motion of the seawater intensifies, and the salt content of its autonomously evaporated water increases. In this case, the hydrogel should maintain a high photothermal conversion rate while improving the selectivity for inorganic salt ions to maintain the low salinity of the condensed water. For Examples 11-14, the PNIPAm structure with temperature-responsive characteristics is fully connected to the MOF unit through grafting treatment, and at the same time forms a good copolymer gel with the hydrogel structure. Its temperature-responsive change characteristics near the low critical solution temperature enable the hydrogel to have different performance emphases at different temperatures to meet the needs of seawater desalination at different temperatures. For Comparative Example 6, the lack of grafting treatment makes the hydrogel unable to show good temperature responsiveness, the photothermal efficiency decreases significantly at low temperatures, and the salinity of condensed water increases significantly at high temperatures, which cannot fully meet the needs of a wider temperature range. Comparative Example 7 shows a similar situation, and because there is no PNIPAm and PVA-cassava starch to form a gel together, the gel component is single, and its comprehensive performance is worse than that of Comparative Example 6. The expansion or contraction of the thermal responsive unit when the temperature changes can adjust the effective surface area of ​​the MOF. When the temperature rises, the hydrophobicity of the thermal responsive unit increases, the water flux of the MOF increases, and the adsorption capacity of inorganic salt ions increases; at low temperatures, the thermal responsive unit shrinks, making the hydrogel more loose as a whole, causing water molecules to be more easily released from the pores of the MOF, thereby accelerating heat exchange and improving the photothermal conversion efficiency.

[0113] Experimental Example 5

[0114] Referring to the experimental steps and methods of Experimental Example 4, seawater desalination experiments were carried out on the hydrogels prepared in Examples 15-18 and Comparative Examples 8-9, and their photothermal conversion efficiencies were recorded respectively and summarized in Table 5.

[0115] The hydrogels prepared in Examples 15-18 and Comparative Examples 8-9 were immersed in seawater at 35°C for 24 hours, then immersed in seawater at 0°C for 24 hours, and placed in seawater at 25°C for 2 hours. The seawater desalination experiment was repeated and the photothermal conversion efficiencies were recorded and summarized in Table 5.

[0116] The hydrogels prepared in Examples 15-18 and Comparative Examples 8-9 were sprayed with metal needles with a diameter of 1 mm at a pressure of 10 / dm 3 The samples were pierced with holes of a density of 1.50 nm and placed in seawater at 25°C for 2 hours before the desalination experiment was repeated. The photothermal conversion efficiencies were recorded and summarized in Table 5.

[0117] The hydrogels prepared in Examples 15-18 and Comparative Examples 8-9 were immersed in seawater adjusted to pH 3.5 for 48 hours, and then placed in seawater at 25° C. for 2 hours before repeating the seawater desalination experiment. The photothermal conversion efficiencies were recorded and summarized in Table 5.

[0118] Table 5 Durability and recyclability of different composite hydrogels

[0119]

[0120] As shown in the cyclability test data of Table 5, the composite hydrogels prepared in Examples 15-18 have significant self-repairing properties, and can maintain performance well after being subjected to high and low temperature cycle treatment, physical damage and acid treatment, which is attributed to the overall composite structure of the hydrogel. For Comparative Example 8, the asynchronous polymerization reaction and gelation process cause the MOF unit with PNIPAm modification to be unable to be effectively combined with the hydrogel body. During the acid treatment process, the MOF part will lose some performance and cannot be restored, and it does not have obvious self-repairing properties for high and low temperature cycles and physical damage. For Comparative Example 9, simple mixing alone makes it impossible for the PNIPAm segment to enter the hydrogel network at all, so its performance loss under harsh conditions cannot be restored by the self-repair of the hydrogel structure. The high degree of compounding of MOF units, PNIPAm units and hydrogel structures is the key to the self-repairing properties of hydrogels. The functions of the three parts are highly integrated through the polymerization process and the gelation process at the same time, with significant synergy, and can work stably under various conditions and have excellent photothermal performance, reflecting the high application value of the hydrogel prepared by the present invention in the field of seawater desalination.

[0121] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a donut-structured hydrogel, characterized in that: The preparation method is as follows: The ZrOCl2·8H2O and fumaric acid were ultrasonically dissolved in solvent A, and multi-walled carbon nanotubes were added and ultrasonically dispersed to obtain a pretreated precursor; The pretreated precursor is subjected to hydrothermal treatment, and then washed and dried to obtain a MOF precursor; The MOF precursor is modified with an acryloyl chloride solution to obtain a modified MOF; The modified MOF is subjected to a grafting treatment to introduce a PNIPAm structure having temperature-responsive characteristics, thereby obtaining MOF801@CNT; The MOF801@CNT is subjected to a thermosensitive cross-linking treatment with polyvinyl alcohol, cassava starch and a cross-linking agent to obtain the donut structure hydrogel.

2. The method for preparing a donut-structured hydrogel according to claim 1, characterized in that: The ultrasonic dissolution process is as follows: by weight, 20-30 parts of the ZrOCl2·8H2O and 10 parts of the fumaric acid are added to 300 parts of the solvent A, and the mixture is treated at an ultrasonic power of 200 W and a frequency of 50 kHz for 5 minutes to obtain a mixed solution A; the ultrasonic dispersion process is as follows: 8 parts of the multi-walled carbon nanotubes are added to the mixed solution A, and the mixture is treated at an ultrasonic power of 300-500 W and a frequency of 60 kHz for 30 minutes at 40°C to obtain the pretreated precursor.

3. The method for preparing a donut-structured hydrogel according to claim 2, characterized in that: The solvent A comprises: N,N-dimethylformamide and formic acid; the volume ratio of the N,N-dimethylformamide to the formic acid is 19:

8.

4. The method for preparing a donut-structured hydrogel according to claim 1, characterized in that: The hydrothermal treatment process is as follows: 350 parts of the pretreated precursor are added into a hydrothermal kettle by mass, the temperature is raised to 130°C at a rate of 10°C / min, and the temperature is kept under autogenous pressure for 7 hours to obtain a hydrothermal precursor; the hydrothermal precursor is cooled to 25°C and centrifuged at a speed of 6000rpm for 5 minutes, the supernatant is removed, and the solid product is retained, which is washed and vacuum dried to obtain the MOF precursor.

5. The method for preparing a donut-structured hydrogel according to claim 4, characterized in that: The vacuum drying process is as follows: after washing the solid product with methanol and N,N-dimethylformamide alternately, the solid product is placed at 60° C. and vacuum dried at a vacuum degree of 95 kPa for 12 hours to obtain the MOF precursor.

6. The method for preparing a donut-structured hydrogel according to claim 1, characterized in that: The modification process is as follows: 20 parts of the MOF precursor are dispersed in 100 parts of dichloromethane by mass, and stirred at a speed of 500 rpm in an ice water bath to obtain a reaction solution A; 30 parts of acryloyl chloride solution are slowly added dropwise to the reaction solution A, and a reaction solution B is obtained after the addition is completed, wherein the dropping rate of the acryloyl chloride solution is 3-5 mL / min; the reaction solution B is heated to 25° C., stirred at a speed of 200 rpm for 16-18 hours, and after removing the solvent, the modified MOF is obtained by washing and drying.

7. The method for preparing a donut-structured hydrogel according to claim 6, characterized in that: The acryloyl chloride solution comprises: acryloyl chloride, dichloromethane, acetonitrile and a trapping agent; the trapping agent comprises: triethylamine and pyridine, wherein the volume ratio of the triethylamine to the pyridine is 3:1; the preparation method of the acryloyl chloride solution comprises: by mass, dissolving 2-3 parts of the acryloyl chloride in 50 parts of the dichloromethane in an ice water bath, stirring at a speed of 350 rpm, then adding 1 part of the trapping agent, and then adding 75 parts of acetonitrile, and mixing evenly to obtain the acryloyl chloride solution.

8. The method for preparing a donut-structured hydrogel according to claim 1, characterized in that: The grafting treatment process is as follows: by weight, 20 parts of the modified MOF are dispersed in 100 parts of the initiator solution, stirred at 200 rpm for 20 minutes at 25°C, 5 parts of N-isopropylacrylamide are slowly added, the temperature is raised to 75°C after mixing evenly, the stirring speed is maintained at 200 rpm for 20 hours, and the solvent is removed and then washed and dried to obtain the MOF801@CNT; the initiator solution includes: azobisisobutyronitrile, potassium persulfate, tetrahydrofuran and N,N-dimethylformamide, wherein the amount of azobisisobutyronitrile added is 3 parts, the amount of potassium persulfate added is 2 parts, the amount of tetrahydrofuran added is 45 parts, and the amount of N,N-dimethylformamide added is 50 parts.

9. The method for preparing a donut-structured hydrogel according to claim 1, characterized in that: The process of the thermosensitive cross-linking treatment is as follows: by weight, 2.5 parts of the MOF801@CNT are dispersed in 100 parts of deionized water, treated at 25°C with an ultrasonic power of 300W and a frequency of 50kHz for 30 minutes, and then 25 parts of the polyvinyl alcohol and 25 parts of the cassava starch are added, stirred at 70°C at a speed of 400rpm for 2 hours, and then 20 parts of the cross-linking agent are added, mixed evenly and allowed to stand at 40°C for 2 hours to obtain the donut structure hydrogel; the cross-linking agent includes: 10 parts of hydrochloric acid and 10 parts of glutaraldehyde solution, wherein the mass concentration of the hydrochloric acid is 5%, and the mass concentration of the glutaraldehyde is 5%; the molecular weight of the polyvinyl alcohol is 80,000-100,000, and the molecular weight of the cassava starch is 600,000-700,000.

10. An application of a donut-structured hydrogel, characterized in that: Application of the donut-structured hydrogel in seawater desalination technology; the donut-structured hydrogel is prepared by the preparation method described in any one of claims 1 to 9; the process for using the donut-structured hydrogel in seawater desalination is: placing the donut-structured hydrogel on the surface of seawater, the bottom of the donut-structured hydrogel is in contact with the seawater, and performing interfacial photoevaporation under solar energy drive.

Citation Information

Patent Citations

  • A graphene oxide / MOF composite membrane, its preparation method and application

    CN109647231B

  • A solar desalination hydrogel and preparation method thereof

    CN115433377B

  • A rapid preparation method of porous composite hydrogel and its application in photothermal desalination

    CN115748257B

  • Method for preparing zirconium-based micro-porous coordination polymer

    CN107400243A

  • Temperature response type MOF-808 composite aerogel as well as preparation method and application thereof

    CN118240266A